A circuit model for SECCM and topographic imaging method in AC mode. (November 2019) - Zhuang, Jian; Liao, Xiaobo; Deng, Yalou; Cheng, Lei; Zia, Ali Akmal; Cai, Yong; Zhou, Maolin
Graphical abstract: Highlights: This paper proposes a single-barrel Scanning electrochemical cell microscope(SECCM) circuit model and verifies this circuit model using the first-order zero-state response in DC mode. An AC scanning mode is proposed to overcome the problem of inaccurate imaging caused by interference in the DC scanning mode. Theoretical analysis is conducted for single-barrel SECCM in DC circuit model and AC circuit model, respectively. The conductive copper strip groove and square boss surface structures were imaged by single-barrel SECCM that was operated in the DC hopping mode and AC hopping mode, respectively. Abstract: Single-barrel scanning electrochemical cell microscopy (SECCM) can be used to perform electrochemical activity analysis and sample surface imaging simultaneously. Compared to SECM & SICM in imaging, the most significant advantage of SECCM is that it does not need to immerse sample in solution, which avoids the electrochemical reaction between electrolyte and sample surface. In traditional direct current (DC) topographic imaging method of SECCM, when the meniscus droplet is contacted with the sample surface, the presence of the redox current determines the Z-height of a scanning point. However, there are some problems in DC mode. Firstly, the redox (Faraday) current is very small (pA/nA), which is susceptible to interference of ambient environment. Secondly, since the inertia of the droplet, the overall height of the imaged topography depends on the droplet size (probe tip diameter) and scanning speed. Therefore, this paper first proposes a single-barrel SECCM circuit model and verifies this circuit model using the first-order zero-state response in the DC mode. Then, an AC scanning mode is proposed, which monitors the change of AC amplitude to determine the Z-height of the scanning point when the meniscus droplet approaches the surface of the sample. The experiments demonstrate that the AC mode has a powerful ability to overcome interference and provide high-stable topographic imaging.